1999
DOI: 10.1086/312111
|View full text |Cite
|
Sign up to set email alerts
|

The Bulge-Disk Orthogonal Decoupling in Galaxies: NGC 4698

Abstract: The R-band isophotal map of the Sa galaxy NGC 4698 shows that the inner region of the bulge structure is elongated perpendicularly to the major axis of the disk, this is also true for the outer parts of the bulge if a parametric photometric decomposition is adopted. At the same time the stellar component is characterized by an inner velocity gradient and a central zero-velocity plateau along the minor and major axis of the disk respectively. This remarkable geometric and kinematic decoupling suggests that a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 22 publications
9
56
1
Order By: Relevance
“…In spite of the low resolution spectroscopy, our results suggest a presence of velocity gradients along the disk major axis for HRG 54103, such as some Sa galaxies (e.g. NGC 4698; NGC 2855; see Bertola et al 1999 andCorsini et al 2002, respectively).…”
Section: Kinematics Of Hrg 54103mentioning
confidence: 54%
See 2 more Smart Citations
“…In spite of the low resolution spectroscopy, our results suggest a presence of velocity gradients along the disk major axis for HRG 54103, such as some Sa galaxies (e.g. NGC 4698; NGC 2855; see Bertola et al 1999 andCorsini et al 2002, respectively).…”
Section: Kinematics Of Hrg 54103mentioning
confidence: 54%
“…(1) at the Observatório do Pico dos Dias (OPD) -Laboratório Nacional de Astrofísica, Brazil, on the 1.6-m telescope using the direct CCD camera with BVRI Kron-Cousins filters (Bessel 1990) and a 384 × 578-pixel chip with a scale of 0.284 arcsec pix −1 (0.128 kpc pix −1 and 0.451 kpc arcsec −1 ); three frames in each filter with individual exposure times of 600 s were taken under photometric conditions better than 1. 2 FWHM seeing; the stars used for extinction and calibration are from Landolt (1992); (2) spectroscopic observations performed at CTIO (Cerro Tololo Inter-American Observatory) with the 1.5-m telescope equipped with a Cassegrain spectrograph and Loral 1k # 1 + Arcon 3.9 (1200 × 800 square pixels, pixel size of 15 μm, scale of 1.3 pix −1 ).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Méndez-Abreu et al (2010) relaxed this condition and found that only 18% of the observed bulges have a probability > 50% of being elongated along the polar axis with no bulges reaching a probability > 90%. In fact, to date NGC 4698 (Bertola et al, 1999), NGC 4672 (Sarzi et al, 2000), and UGC 10043 (Matthews & de Grijs, 2004) are the only spiral galaxies known to host a prominent bulge sticking out from the plane of the disc.…”
Section: Polar Bulgesmentioning
confidence: 99%
“…McDermid et al (2006) found NDs and counter-rotating cores in the central kpc of earlytype galaxies and evidence for recent circum-nuclear star formation. The presence of dynamically decoupled features such as a counter-rotating disc in NGC 4458 (Morelli et al 2004, c 0000 RAS 2010) and a disc rotating perpendicular to the main galactic disc (Bertola et al 1999;Pizzella et al 2002;Corsini et al 1999Corsini et al , 2012 can be explained by the capture of external gas. However interactions may not be the main mechanisms driving gas to nuclei in more isolated galaxies, where observations show that there is continuing star formation in some NDs e.g.…”
Section: Introductionmentioning
confidence: 99%